2006
DOI: 10.1080/09603120600641334
|View full text |Cite
|
Sign up to set email alerts
|

Air particulate pollution due to bushfires and respiratory hospital admissions in Brisbane, Australia

Abstract: To examine the impact of bushfire smoke on hospital admission rates for respiratory disease, a time series study was conducted in Brisbane, Australia. Data on particles of 10 microns or less in aerodynamic diameter (PM10) per cubic metre, bushfire events, meteorological conditions, and daily respiratory hospital admissions were obtained for the period of 1 July 1997 to 31 December 2000. A generalized linear model with the negative binomial distribution was used to estimate the effects of bushfire smoke on resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 39 publications
(69 reference statements)
3
58
0
2
Order By: Relevance
“…36 In general, the epidemiological models to estimate the health outcomes of air pollution give lower risks in Europe than in the United States, with the lowest effects being observed in Australia. 37,38 This may suggest exposition to different pollution levels and diverse susceptibilities of the populations. On the other hand, these observations indicate that conclusions within a particular country may not be willingly assignable to other regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In general, the epidemiological models to estimate the health outcomes of air pollution give lower risks in Europe than in the United States, with the lowest effects being observed in Australia. 37,38 This may suggest exposition to different pollution levels and diverse susceptibilities of the populations. On the other hand, these observations indicate that conclusions within a particular country may not be willingly assignable to other regions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, these observations indicate that conclusions within a particular country may not be willingly assignable to other regions. 37 Therefore, more research is needed to infer specific regional links between air pollution and adverse health effects. Considering the uncertainties about the health effects of air pollutants and given the fact that this kind of investigation is rather inexistent in Portugal, a study was performed using Poisson time series regression models for the complete study population, and for subgroups, admitted to hospital emergencies for cardiorespiratory illness in Lisbon during 1999-2004.…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with cellular and ultrastructural modifications in leaves, reduced stomata opening and CO 2 assimilation, reduced chlorophyll concentration, chlorosis and leaf necrosis (Vitorello et al, 2005;Chen, 2006;Miyasaka et al, 2007;Chen et al, 2010). Accessions IT97K-568-18, TVU-9256 and IT98K-555-1 had 100% emergence under the control with respect to other treatments in contrast to TVU-4886 (93.3%) and IT96-610 (80%) as shown in Table 1.…”
Section: Resultsmentioning
confidence: 98%
“…Most of the health impacts have been observed in vulnerable groups of people (especially the elderly and people with preexisting health conditions) (Delfino et al, 2009;Ignotti et al, 2010;Do Carmo et al, 2013;Rappold et al, 2011;Kochi and Champ, 2012;Rappold et al, 2012). Indeed, the adverse health impacts due to PM related wildfire smoke exposure have been observed at comparatively low PM concentrations, well within current air quality standards (Chen et al, 2006;Johnston et al, 2006, Naeher et al, 2007Morgan et al, 2010). Studies have also shown that slight increases of particulates from wildfire smoke were associated with increased incidence of hospital admissions for respiratory conditions especially asthma (Johnston et al, 2006;Chen et al, 2006).…”
Section: What Could Be the Impact Of Smoke From Prescribed Burning Onmentioning
confidence: 83%